Artificial Intelligence: A neoteric reach in Periodontics - Dr. Lavanya Boyeena , Dr. K. Phani Yasaswini , Boyeena Nitin Sagar, Dr. Akhila Mydukuru, Katuri Sreeja, Muthyala Rohith (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Periodontal disease diagnosis is the fundament point for the accurate treatment planning. Precise diagnosis requires experience and knowledge of the dentist, But it may vary from each dentist to the other dentist causing errors in diagnosis and treatment planning. To overcome these limitations, an emerging technology like Artificial Intelligence(AI) is of immense use in the field of periodontics. In this technology, an Artificial Intelligence driven machine can be utilized for performing the human tasks perfectly. This review is an attempt to describe various current concepts and future applications of AI in periodontology